Delineation of aquifer vulnerability to pollution: A case study in Eha Alumona, Nsukka Local Government Area, Enugu State, Nigeria - Okwudili Cornelius Ossai; Daniel Nnaemeka Obiora; Francisca Nneka Okeke; Johnson Cletus Ibuot (EQA)
This study aims to assess the vulnerability of aquifers to contamination in Eha Alumona, Nsukka Local Government Area, Enugu State, Nigeria, using resistivity data and various vulnerability indices. The VES survey conducted across fifty stations revealed five distinct geo-electric layers, with resistivity values ranging from 5.7 to 87,620.9 Ωm, and depths varying from 0.4 to 234.5 m. The study's findings indicate that the first two layers are characterized by low resistivity values, suggesting the presence of surface materials such as sandy soil and weathered rock, which are likely to contain moisture and exhibit varying porosity. The lower layers show higher resistivity values, pointing to more consolidated or less permeable geological materials. The vulnerability assessment, based on four indices (GOD, GLSI, DRIST, and SI), reveals that the aquifer is generally low in vulnerability across the study area. The GOD index suggests low contamination risk due to deep water tables and protective layers. The GLSI and DRIST indices further indicate moderate to low susceptibility, with 62% and 64% of the study area being classified as moderately susceptible, respectively. The SI index also supports these findings, categorizing the aquifer as well-protected from contamination. Overall, the results emphasize the importance of monitoring and sustainable management practices to ensure the long-term protection of groundwater resources in the region.